Highly resolved measurements of dust motion in the sheath boundary of magnetized plasmas. (8th September 2015) - Shalpegin, A.; Brochard, F.; Ratynskaia, S.; Tolias, P.; De Angeli, M.; Vignitchouk, L.; Bykov, I.; Bardin, S.; Bystrov, K.; Morgan, T.; De Temmerman, G.
Abstract: Dust trajectories have been recorded with an unprecedented, under fusion-relevant plasma conditions, spatial resolution of 9 μ m/pixel in Pilot-PSI. The optical setup allowed the use of fast cameras as a basic microscope. It is demonstrated that such a resolution is essential for the correct interpretation of experiments on several aspects of dust-surface interactions. Highly resolved tungsten dust dynamics measurements are presented from dedicated experiments on dust collisions with plasma facing components, motion in the vicinity of castellated samples and remobilization from planar samples.